Sensitivitas Metode Serologi dan Polymerase Chain Reaction untuk Mendeteksi Bean Common Mosaic Potyvirus pada Kacang Panjang - Sherli Anggraini; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2014)
Mosaic disease in yard long bean is caused by Bean common mosaic potyvirus (BCMV) and has been reported to affect yield. Common method to detect infection of BCMV involves serological assay and polymerase chain reaction (PCR). The aims of this research is to assess the sensitivity of three methods, i.e. Indirect Enzym-Linked Immunosorbent Assay (I-ELISA), Dot Immunobinding Assay (DIBA), and reverse transcription (RT)-PCR as detection method for BCMV infection in yard long bean. Sensitivity level of the methods was evaluated by diluting plant extract and antisera for I-ELISA and DIBA, and cDNA as template in RT-PCR. Virus isolate from Cirebon was maintained in yard long bean in screenhouse and used for the assessment. Absorbance value of ELISA showed that dilution end point for I-ELISA was reached at 10-3 and 10-2 of plant extract and antisera dilution, respectively. Positive infection was still detected using DIBA when the plant extract was diluted up to 10-5 based on development of color intensity on nitrocellulose membrane. Specific viral DNA fragment was still amplified when cDNA was diluted up to 10-4, indicated higher sensitivity level of RT-PCR method.